Jesus of Nazareth in New Testament preaching - Stanton, Graham (Society for New Testament Studies monograph series, 1974)
This book argues that an account of the life and character of Jesus formed an integral part of the early church's preaching. Against many modern scholars, Dr Stanton seeks to show that interest in the life of Jesus was not a late development within primitive Christianity. A study of Luke's Gospel indicates that in his own day reference to the life and character of Jesus was an important part of missionary preaching. In this respect at least, Luke was no innovator. The references in the speeches in Acts to the life of Jesus can be traced to Luke's use of earlier traditions. Dr Stanton then takes up the much-debated question of Paul's interest in Jesus of Nazareth. The author challenges several widely-accepted views from critical conclusions about the nature and purpose of the traditions on which the evangelists drew.